Introducing Multidisciplinary Oncology Management to the Medical Student - Michael J. LaRiviere, MD; Patricia Mae G. Santos, MD; Joshua A. Jones, MD; John Nicholas Lukens, MD; Neha Vapiwala, MD; Samuel D. Swisher-McClure, MD, MSHP; Abigail T. Berman, MD, MSCE (Advances in Radiation Oncology, 2020)
Despite the fact that a large portion of medical students pursue training in a cancer-related discipline, oncology is emphasized to a disproportionately lesser extent than are other disciplines in medical school. Medical students have wide gaps in their oncology-specific knowledge, and undergraduate medical education fails to address the multidisciplinary nature of oncology. To address these shortcomings and improve medical students’ understanding of the multidisciplinary nature of oncology, we have instituted a clinical oncology elective for medical students: an optional, 2-day session held after classes and promoted by student interest groups. Day 1 comprised a series of short faculty lectures beginning with the concepts of and rationale for staging, an approach to breaking bad news, guideline-based management, and multidisciplinary tumor board discussion. Three multidisciplinary tumor boards were simulated on the second day, run by attending surgeons, medical oncologists, and radiation oncologists with expertise in the cancer of interest, using real patient examples. Ultimately, the clinical oncology elective shows medical students how the oncology care team works together to care for cancer patients.